Awareness about mosquito-borne infections among agricultural and horticultural college students: Coimbatore, South India - Palaniappan, V.; Kalidas, P.; Lokeshwaran, R. S. (International Journal Of Community Medicine And Public Health, 2018)
Background: Mosquito-borne infections especially dengue has created several outbreaks in the present days. Agricultural and horticultural college students are at increased risk of getting infected since they are involved in a lot of field activities. The main aim of our study is to assess the awareness about mosquito-borne infections among agricultural and horticultural students of all the academic years. Also, to analyse the preventive measures and sanitary methods followed by the students to prevent the infection. Methods: This cross-sectional study was conducted in Tamil Nadu Agricultural University (TNAU), Coimbatore including 250 students who are involved in the field works. The questionnaire consisting of 24 multiple choice questions were distributed and collected after filling. The data were processed and statistical significance was calculated using the software SPSS version 20. Results: Females have comparatively good knowledge (54.8%) than males (46.9%). Students whose age is less than 20 years have good knowledge (64%) when compared to students with age more than or equal to 20 years (40.8%). Agricultural students have comparatively fair knowledge (54.5%) than Horticultural students (47.1%). There is a significant association between knowledge and age. Conclusions: The results of our study revealed that the students have fair level of knowledge about mosquito-borne infections especially dengue. Not only creating awareness is important, it should also be looked into that people implement their knowledge into day-to-day practice to prevent the mosquito-borne infections.